2019
DOI: 10.1371/journal.pone.0217861
|View full text |Cite
|
Sign up to set email alerts
|

Pose estimates from online videos show that side-by-side walkers synchronize movement under naturalistic conditions

Abstract: Marker-less video-based pose estimation promises to allow us to do movement science on existing video databases. We revisited the old question of how people synchronize their walking using real world data. We thus applied pose estimation to 348 video segments extracted from YouTube videos of people walking in cities. As in previous, more constrained, research, we find a tendency for pairs of people to walk in phase or in anti-phase with each other. Large video databases, along with pose-estimation algorithms, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 39 publications
1
34
0
Order By: Relevance
“…Another "in the wild example" is given by a recent study by Chambers et al (86), who revisited the classic question of how people synchronize their walking, but with a modern twist by using videos from YouTube and analysis with OpenPose (19). Consistent with studies performed in the laboratory, they found a tendency for pairs of people to either walk in or exactly out of phase (86).…”
Section: Natural Behaviors and Ethologically Relevant Featuresmentioning
confidence: 74%
“…Another "in the wild example" is given by a recent study by Chambers et al (86), who revisited the classic question of how people synchronize their walking, but with a modern twist by using videos from YouTube and analysis with OpenPose (19). Consistent with studies performed in the laboratory, they found a tendency for pairs of people to either walk in or exactly out of phase (86).…”
Section: Natural Behaviors and Ethologically Relevant Featuresmentioning
confidence: 74%
“…Some prior studies have used OpenPose to investigate particular features of walking or other human movement patterns (Chambers et al, 2019;Sato et al, 2019;Viswakumar et al, 2019;Nakano et al, 2020;Ota et al, 2020;Zago et al, 2020). Our findings align with these reports in that we found OpenPose to be capable of reasonably accurate tracking of human movement (in our case, walking).…”
Section: Discussionmentioning
confidence: 99%
“…OpenPose is a freely available human pose estimation algorithm that uses Part Affinity Fields to detect up to 135 keypoints in images of humans (Martinez et al, 2017;Cao et al, 2019). Several prior studies have used OpenPose to study certain features of human walking (Chambers et al, 2019;Sato et al, 2019;Viswakumar et al, 2019;Zago et al, 2020), but there remain important needs for robust validation of a comprehensive set of gait parameters against motion capture measurements and a shareable workflow. First, we used OpenPose to detect keypoints on videos of healthy adults walking overground.…”
Section: Introductionmentioning
confidence: 99%
“…By creating such a 'normative' database, we can then estimate the probability that the movements of a new infant belong to the normative distribution, thereby assessing the probability that the infant is healthy. In previous work, we have shown that online video databases are a useful source of human movement data [27]. In the present study, we built a normative database of infant movements based on video data of infants from YouTube, assuming that found videos represented healthy infant movement.…”
Section: A Youtube Datamentioning
confidence: 99%